Analysis of the Effectiveness of Online Teaching Based on Big Data. Issue 3 (April 2021) - Zhang, Hanping
Abstract: Online teaching is a new teaching method that has emerged with the development of the Internet. Online teaching can realize remote teaching with the help of a network platform, which can not only meet the learning needs of students anytime and anywhere, but also achieve the purpose of teacher-student interaction and personalized teaching. Applying big data to online teaching can undoubtedly improve teaching efficiency to the greatest extent. This article will analyze the effectiveness of online teaching based on big data, and point out that the use of big data analysis can improve the pertinence of teaching and improve the effectiveness of online teaching. Effectiveness improves the quality of teaching.